2015
DOI: 10.17933/bpostel.2013.110301
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Quality of Experience Layanan Telekomunikasi Seluler Masyarakat Kabupaten Kepulauan Sangihe

Abstract: Abstract-Universal Service Obligation (USO) requires all telecommunication network operators and service providers to contribute in providing facilities and universal telecommunication infrastructures. Telecommunication service's performances, particularly for mobile services need to be studied because they have important position in information exchange flow, especially in borderlands that are valuable to information gap. With descriptive survey and quantitative approach, the aim of this research is to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Therefore, when accessing the network, user satisfaction needs to be considered. User satisfaction can be assessed by quality of experience (QoE) [2]. QoE mainly focuses on multimedia applications and network communications; people put those who use internet products in the role of users [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when accessing the network, user satisfaction needs to be considered. User satisfaction can be assessed by quality of experience (QoE) [2]. QoE mainly focuses on multimedia applications and network communications; people put those who use internet products in the role of users [3].…”
Section: Introductionmentioning
confidence: 99%
“…identified that around 30% of households subscribing to fixed broadband in Australia will consider switching to wireless broadband services, especially since the launch of of wireless services. Apart from technology, high user mobility is the reason for the increase in cellular users (R. A Wahab, 2013)…”
mentioning
confidence: 99%
“…of wireless services. Apart from technology, high user mobility is the reason for the increase in cellular users (R. A Wahab, 2013)…”
mentioning
confidence: 99%